Synthesis and Characterization of Some Dicarboxylato and Salicylato Derivatives of Antimony Triochloride Adducts - Dabas, P.; Rastogi, M.K. (Asian Journal of Chemistry, 2010)
Dicarboxylato and salicylato chelates of some antimony trichloride adducts have been prepared. The antimony trichloride adducts used were with anthracene, aniline, benzamide, pyridine, thiourea and DMSO. The disodium salts of oxalic, succinic, adipic, tartaric, salicylic and phthalic acids were used. The physical characteristics and IR, UV spectra of the complexes are reported. The nature of the metal-carboxyl group linkage is discussed.